Architecture in Dialogue with an Activated Ground Unreasonable Creatures - Bette, Urs (UCL Press, 2020)
Architecture in Dialogue with an Activated Ground sets out to validate the role of the unreasonable in the design process. Using case study projects, architect Urs Bette gives an insight into the epistemological processes of his creative practice, and unveils the strategies he deploys in order to facilitate the poetic aspects of architecture within a discourse whose evaluation parameters predominantly involve reason. Themes discussed include the emergence of space from the staged opposition between the architectural object and the site, and the relationship between emotive cognition and analytic synthesis in the design act. In both cases, there is a necessary engagement with forms of 'unreasonable' thought, action or behaviours.